2020
DOI: 10.1523/jneurosci.0309-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Doc2 Proteins Are Not Required for the Increased Spontaneous Release Rate in Synaptotagmin-1-Deficient Neurons

Abstract: Regulated secretion is controlled by Ca 2ϩ sensors with different affinities and subcellular distributions. Inactivation of Syt1 (synaptotagmin-1), the main Ca 2ϩ sensor for synchronous neurotransmission in many neurons, enhances asynchronous and spontaneous release rates, suggesting that Syt1 inhibits other sensors with higher Ca 2ϩ affinities and/or lower cooperativities. Such sensors could include Doc2a and Doc2b, which have been implicated in spontaneous and asynchronous neurotransmitter release and compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
3
3
0
Order By: Relevance
“…Previously, we concluded that changes in spontaneous release rates after genetic or biochemical manipulations did not correspond with the energy barrier shifts measured with HS ( Schotten et al, 2015 ). Here we showed both in Syt1 KO ( Figure 1 ) and Syt1 9Pro expressing synapses ( Figure 2 ) that mEPSC frequencies were increased, in line with previous studies in autapses ( Ruiter et al, 2019 ; Díez-Arazola et al, 2020 ; Huson and Cornelisse, 2019 ) and networks ( Xu et al, 2009 ; Bai et al, 2016 ; Liu et al, 2014 ; Courtney et al, 2018 ). It remains enigmatic why others found a similar increase in spontaneous release in networks but not in autapses after Syt1 deletion ( Liu et al, 2009 ; Wierda and Sørensen, 2014 ), but differences in culture protocol ( Bekkers, 2020 ), or genetic background could play a role.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previously, we concluded that changes in spontaneous release rates after genetic or biochemical manipulations did not correspond with the energy barrier shifts measured with HS ( Schotten et al, 2015 ). Here we showed both in Syt1 KO ( Figure 1 ) and Syt1 9Pro expressing synapses ( Figure 2 ) that mEPSC frequencies were increased, in line with previous studies in autapses ( Ruiter et al, 2019 ; Díez-Arazola et al, 2020 ; Huson and Cornelisse, 2019 ) and networks ( Xu et al, 2009 ; Bai et al, 2016 ; Liu et al, 2014 ; Courtney et al, 2018 ). It remains enigmatic why others found a similar increase in spontaneous release in networks but not in autapses after Syt1 deletion ( Liu et al, 2009 ; Wierda and Sørensen, 2014 ), but differences in culture protocol ( Bekkers, 2020 ), or genetic background could play a role.…”
Section: Discussionsupporting
confidence: 91%
“…1) and Syt1 9Pro expressing synapses (Fig. 2) that mEPSC frequencies were increased, in line with previous studies in autapses [5,20,55] and networks [28,29,36,56]. It remains enigmatic why others found a similar increase in spontaneous release in networks but not in autapses after Syt1 deletion [57,58], but differences in culture protocol [59], or genetic background could play a role.…”
Section: Changes In Spontaneous Release Do Not Directly Correspond Tosupporting
confidence: 86%
“…1) and Syt1 9Pro expressing synapses (Fig. 2) that mEPSC frequencies were increased, in line with previous studies in autapses [5,20,55] and networks [28,29,36,56]. It remains enigmatic why others found a similar increase in spontaneous release in networks but not in autapses after Syt1 deletion [57,58], but differences in culture protocol [59], or genetic background could play a role.…”
Section: Changes In Spontaneous Release Do Not Directly Correspond Tosupporting
confidence: 87%
“…9 ), indicating that SNT-1 still functions as a fast Ca 2+ sensor even when it is not tethered on SVs. Interestingly, the cytoplasmic region of vertebrate Syt1 retains the ability to synchronize SV release in response to a train stimulus ( Díez-Arazola et al, 2020 ). In contrast, we show that SNT-3 is cytoplasmic but mediates delayed neurotransmitter release.…”
Section: Discussionmentioning
confidence: 99%